Targeted education methods for the enhanced understanding of asthma - Rauschenberg, Abigail, author; Maresh, Ryan, advisor (Colorado State University. Libraries, 2025)
Asthma is a chronic disease characterized by episodes of wheezing, coughing, and shortness of breath. This disease is highly prevalent in both adult and pediatric populations and can affect the day-to-day life of those afflicted. This paper serves to explore the pathophysiology of asthma, particularly the roles of bronchoconstriction, airway inflammation, and the immune response associated with it. Diagnostic techniques and classification of asthma are also discussed, particularly related to different phenotypic presentations of the disease. Treatment options and plans are also identified. Beyond the physical, the psychosocial elements of having a chronic disease are discussed, emphasizing the emotional challenges faced by adolescents. Taking the physical and psychosocial elements into consideration, the need for targeted education techniques is highlighted and explored. By combining the biological and psychosocial perspectives regarding adolescent chronic asthma, this paper advocates for a change to the patient-care approach for asthmatics.
Keywords: asthma; chronic disease; integrated care; psychosocial impact; patient education